2016
DOI: 10.3390/ijms17081302
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiprotic Novel Chitosanase from Bacillus mycoides and Its Application in the Production of Chitooligomers with Their Antioxidant and Anti-Inflammatory Evaluation

Abstract: The objectives of this investigation were to produce a novel chitosanase for application in industries and waste treatment. The transformation of chitinous biowaste into valuable bioactive chitooligomers (COS) is one of the most exciting applications of chitosanase. An amphiprotic novel chitosanase from Bacillus mycoides TKU038 using squid pen powder (SPP)-containing medium was retrieved from a Taiwan soil sample, which was purified by column chromatography, and characterized by biochemical protocol. Extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…In our previous study [3], we discovered chitosan oligomers with a low degree of polymerization that showed both antioxidant and anti-inflammatory activity. In this study, the anti-inflammatory activity of Fraction 4-4 (HGA) was estimated using an in vitro model: LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study [3], we discovered chitosan oligomers with a low degree of polymerization that showed both antioxidant and anti-inflammatory activity. In this study, the anti-inflammatory activity of Fraction 4-4 (HGA) was estimated using an in vitro model: LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was vigorously shaken and incubated for 30 min in the dark, and the absorbance was then measured at 517 nm against a blank [3]. The scavenging ability was calculated as described in our previous paper [3]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture was kept in the dark for 30 min before absorbance at 517 nm was measured [39]. Radical scavenging activity was calculated using the following formula:Antioxidant activity (%) = [(AB  AA)/AB] × 100 where AB and AA stand for absorption of the blank sample ( t = 0 min) and absorption of the tested sample solution ( t = 30 min), respectively.…”
Section: Methodsmentioning
confidence: 99%